Culicidae (Diptera) em área de barragem em Santa Catarina e no Rio Grande do Sul - Gomes, Almério C (2009)
The Culicidae composition of the Barra Grande Lake situated between the municipalities of Esmeralda (Rio Grande do Sul State) and Anita Garibaldi (Santa Catarina State) was assessed by monthly samplings. Twenty-four species were identified from a total of 1,185 specimens (74.7% as adults and 25.3% as immatures), with Aedes fluviatilis Lutz as the most frequent species. Several species are new records, and some of them are of public health interest. It is suggested that local environmental changes may alter the relationship between humans and vector mosquitoes.